2015
DOI: 10.1021/acsmedchemlett.5b00171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bidentate Salicylic Acid Inhibitors of PTP1B

Abstract: PTP1B is a master regulator in the insulin and leptin metabolic pathways. Hyper-activated PTP1B results in insulin resistance and is viewed as a key factor in the onset of type II diabetes and obesity. Moreover, inhibition of PTP1B expression in cancer cells dramatically inhibits cell growth in vitro and in vivo. Herein, we report the computationally guided optimization of a salicylic acid-based PTP1B inhibitor 6, identifying new and more potent bidentate PTP1B inhibitors, such as 20h, which exhibited a > 4-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…92,93 They generated several inhibitors, the best of which ( 27) inhibited PTP1B with an IC 50 of 1.7 μM; however, despite using multiple salicylates to target both pTyr-binding pockets, these compounds were not selective for PTP1B over TC-PTP. 93 Glioblastoma multiforme (GBM) is an aggressive brain malignancy which is often characterized by constitutive STAT3 activation. Thus, GBM represents an important possible therapeutic indication for STAT3 inhibitors.…”
Section: Salicylates and Related Compoundsmentioning
confidence: 99%
“…92,93 They generated several inhibitors, the best of which ( 27) inhibited PTP1B with an IC 50 of 1.7 μM; however, despite using multiple salicylates to target both pTyr-binding pockets, these compounds were not selective for PTP1B over TC-PTP. 93 Glioblastoma multiforme (GBM) is an aggressive brain malignancy which is often characterized by constitutive STAT3 activation. Thus, GBM represents an important possible therapeutic indication for STAT3 inhibitors.…”
Section: Salicylates and Related Compoundsmentioning
confidence: 99%
“…Monomeric thioureas I–III and squaramides sq- I –sq- III were prepared (Scheme ), in two steps from 1 , easily obtained by reaction of commercially available 4-amino-2,6-dichlorophenol with 4-vinylbenzyl chloride and t -BuOK in DMF at 0 °C …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that some molecules having 1,2,3-triazoles ( 4 – 6 , Fig. 1 ) (Rao et al 2014 ; Haftchenary et al 2015 ; Shafi et al 2012 ) also showed good anti-inflammatory properties. Considering the individual biological activities, medicinal importance of ibuprofen and 1,4-disubstituted 1,2,3-triazoles, we designed novel class of small molecules ( 7 , Fig.…”
Section: Introductionmentioning
confidence: 94%